2003
DOI: 10.1074/jbc.m212508200
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Stability Relationships in Extremophilic Enzymes

Abstract: Psychrophilic, mesophilic, and thermophilic ␣-amylases have been studied as regards their conformational stability, heat inactivation, irreversible unfolding, activation parameters of the reaction, properties of the enzyme in complex with a transition state analog, and structural permeability. These data allowed us to propose an energy landscape for a family of extremophilic enzymes based on the folding funnel model, integrating the main differences in conformational energy, cooperativity of protein unfolding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
390
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 427 publications
(439 citation statements)
references
References 48 publications
37
390
4
2
Order By: Relevance
“…It has been shown that stabilization induced by acarbose binding closely follows the activation parameters of the amylolytic reaction (22) between the ground state (free enzyme) and the transition state intermediate (enzyme-acarbose complex). The thermograms of AHA and of its mutants were therefore recorded by DSC in the presence of acarbose (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that stabilization induced by acarbose binding closely follows the activation parameters of the amylolytic reaction (22) between the ground state (free enzyme) and the transition state intermediate (enzyme-acarbose complex). The thermograms of AHA and of its mutants were therefore recorded by DSC in the presence of acarbose (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GdmCl-induced unfolding was monitored at 20°C after overnight incubation of the samples at this temperature in 30 mM MOPS, 50 mM NaCl, 1 mM CaCl 2 , pH 7.2, on an LS50B spectrofluorometer (PerkinElmer Life Sciences) (22). The equilibrium condition was ascertained by recording unfolding as a function of time.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations